The Implementation of Savings and Loan Services by the Salayo Sepakat Village-Owned Enterprise under Government Regulation Number 11 of 2021 concerning Village Owned Enterprises in Nagari Salayo - Efendi, Gebyanti; Aermadepa, Aermadepa; Nizwana , Yulia (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2026)
Village-Owned Enterprises are mandated in Government Regulation Number 11 of 2021. Based on Article 1, BUMDes is a business entity whose capital comes from separated village assets. The existence of BUMNagari Salayo Sepakat in Nagari Salayo plays a role in improving the community's economy, but in its implementation there are still problems in the savings and loan unit, namely the existence of credit congestion so that payments do not match the agreed initial. The formulation of the problem discussed in this paper is how the implementation of savings and loans and what are the obstacles and efforts made in the implementation of savings and loans by the Nagari Salayo Sepakat Enterprises according to Government Regulation Number 11 of 2021 concerning Village-Owned Enterprises in Nagari Salayo. The approach method used by researchers in this study is sociological (empirical), an approach that is legal research that functions to look at the law in the implementation of savings and loans by the Nagari Salayo Sepakat Enterprises according to Government Regulation Number 11 of 2021 concerning Village-Owned Enterprises in Nagari Salayo. The research results show that (1) the implementation of savings and loans by the Salayo Sepakat Village-Owned Enterprise (BUMN) includes (a) gathering members for savings and loans, (b) collecting savings, (c) applying for loans through direct applications, (d) verifying and approving loans, (e) disbursing loan funds, and (f) repayment and monitoring of loans. (2) Obstacles to the implementation of savings and loans by the Salayo Sepakat Village-Owned Enterprise (BUMN) include low community participation and trust, low member financial literacy, limited human resources for managers, a high risk of non-performing loans, and suboptimal governance and SOPs. Efforts to overcome these obstacles include increasing outreach, member mentoring, strengthening human resources, credit selection, and developing SOPs, in accordance with Government Regulation Number 11 of 2021concerning Village-Owned Enterprises in Nagari Salayo.